Penguatan Sumber Daya Manusia dengan Pendekatan Asset Based Community Development (ABCD) - Khairi; Hidayat, Nurul; Ainul Yaqin, Moh.; Yaqin, Ainul; Alam, Bahrul; Fairus, Jihan; Putri Utami, Redita (Universitas Pangeran Diponegoro Nganjuk, 2025)
This community service program was implemented to enhance human resource potential through the Asset Based Community Development (ABCD) approach. Gelam Village, located in Tambak District, possesses diverse assets that have not been fully utilized, particularly in relation to the development of youth interests and talents. The lack of adequate facilities and platforms has limited opportunities for children and adolescents to express their creativity and develop their potential. Therefore, this program was designed to provide solutions by leveraging local assets and community strengths. The program was carried out using the ABCD method, which emphasizes the identification, mapping, and optimization of existing community assets. Activities included skill development training, competitions organized in celebration of the holy month of Ramadan, and art performances involving active participation from community members. The primary beneficiaries of these activities were children and youth with talents in arts, sports, and other creative skills. The findings indicate that the program was effective in increasing community participation. This was reflected in the large number of participants joining the competitions as well as the enthusiasm of audiences attending the events. Furthermore, the activities successfully identified promising young talents who can be further nurtured to represent the village in higher-level competitions. The program also fostered greater social cohesion and provided a platform for community members to strengthen their identity through cultural and creative expressions. In conclusion, the implementation of the ABCD approach proved to be an effective strategy for community empowerment by strengthening human resources based on local assets and potentials. The outcomes highlight the importance of asset-oriented methods in building sustainable community development initiatives.